2010
DOI: 10.1073/pnas.1002494107
|View full text |Cite
|
Sign up to set email alerts
|

Immune-related zinc finger gene ZFAT is an essential transcriptional regulator for hematopoietic differentiation in blood islands

Abstract: TAL1 plays pivotal roles in vascular and hematopoietic developments through the complex with LMO2 and GATA1. Hemangioblasts, which have a differentiation potential for both endothelial and hematopoietic lineages, arise in the primitive streak and migrate into the yolk sac to form blood islands, where primitive hematopoiesis occurs. ZFAT (a zinc-finger gene in autoimmune thyroid disease susceptibility region / an immune-related transcriptional regulator containing 18 C 2 H 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 52 publications
(53 reference statements)
3
32
0
1
Order By: Relevance
“…The ZFAT gene has been found to play a transcriptional regulator role for immune regulation and apoptosis. 30 ZFAT might be involved in development of mesodermal cells, 31 and hence may affect development of muscle and connective tissue of the pelvic floor. The collagen XVIII ( COL18A1 ) gene is another interesting candidate gene for POP.…”
Section: Discussionmentioning
confidence: 99%
“…The ZFAT gene has been found to play a transcriptional regulator role for immune regulation and apoptosis. 30 ZFAT might be involved in development of mesodermal cells, 31 and hence may affect development of muscle and connective tissue of the pelvic floor. The collagen XVIII ( COL18A1 ) gene is another interesting candidate gene for POP.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated that Zfat-deficiency (Zfat -/-) is lethal for mice by embryonic day (E) 8.5, with a reduction in the number of blood islands and hematopoietic progenitor cells. ZFAT directly regulates the transcription factors including Tal1, Lmo2 and Gata1 in the blood islands [6]. We also reported that ZFAT is essential for endothelial cell assembly and the branch point formation of capillary-like structures in an angiogenesis model, suggesting that ZFAT is a critical transcriptional regulator for endothelial differentiation [7].…”
Section: Introductionmentioning
confidence: 93%
“…3). ZFAT is highly conserved among ZFAT orthologues from fish to mammalian species [4], and Zfat -/-mice die by embryonic day (E) 8.5 [6], indicating that ZFAT plays pivotal roles in mouse development. ZFAT knockdown by small interfering RNA in MEFs induced apoptosis, supporting the hypothesis that ZFAT is essential for cell survival and plays a critical role in mesoderm-derived cells and mesenchymal cells.…”
Section: Genes Regulated By Zfat In the Functions Of Apoptosis Cell mentioning
confidence: 99%
See 2 more Smart Citations